MODIFIKASI MESIN PENGADUK DODOL SKALA INDUSTRI RUMAH TANGGA - Haerani, Benarti; Jamaluddin, Jamaluddin; Suardy, Suardy (Universitas Negeri Makassar, 2019)
Dodol is a traditional food that is quite popular in several regions in Indonesia. Dodol is one ofÂ agricultural products the processed which is included in the type of food that has a rather wet nature. One of the difficulties in processing dodol is the stirring process which takes a long time and must be carried out continuously. Therefore, research on dodol stirrer is needed so that it can simplify the dodol stirring process. This study aims to determine the mechanism of modification stirrer dodol household scale industrial stirrers and effective and efficient work method. The form of this research is tool modification. The research data was obtained from the results of a comparison testing of dodol manually and using the dodol stirrer. The parameters tested in this study are the weight of the material processed and the time needed to proces dodol. Data analysis techniques are carried out quantitatively with descriptive statistics. The results showed that the effectiveness of dodol making using the dodol stirrer machine was 24 grams / minute and the efficiency of the dodol production obtained was 67.8%.